2009
DOI: 10.11646/zoosymposia.2.1.40
|View full text |Cite
|
Sign up to set email alerts
|

<strong>Biodiversity of polychaetous annelids from the peninsula of Cap Bon, northeast coast of Tunisia</strong>

Abstract: in Tunisia, polychaete studies are very rare (Fauvel 1924 a, b; Westheide 1972; Zibrowius 1970, 1971; Cantone 1978; Ben Amor 1984; Zaâbi & Afli 2005). The aim of this study was to update and fill in gaps in data of polychaetes of Tunisia. Samples were taken aboard the research vessel R/V Hannibal with a Van Veen grab (0.1 m²) and a core (0.009 m²). Nine sites located on the peninsula of Cap Bon on the NE coast of Tunisia, from Sidi Daoud to Ras Lahmer, were sampled in 2005 and 2006. A total of 5,920 indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…The species in question belong to the collection of Ayari and Zaâbi (RF in Table 1). 3-Research on polychaetes and studies dealing with macrobenthic fauna, which were published after the last complete inventory of Tunisian polychaetes due to Ayari et al (2009), are revised and collated here, especially the data of Diawara et al (2008), Pérez-Domingo et al (2008, Ayari et al (2009), Zaâbi et al (2009Zaâbi et al ( , 2010Zaâbi et al ( , 2012, Khedhri et al (2014Khedhri et al ( , 2016Khedhri et al ( a, b, 2017, Mosbahi et al (2015Mosbahi et al ( a, b, 2017, Ounifi-Ben Amor et al (2015), Boudaya et al (2019), and Chaibi et al (2019. Other papers were consulted to check the distribution of species in other regions of the Mediterranean (e.g., Castelli et al, 2008;Çinar et al, 2014a, b;Mikac, 2015;Faulwetter et al, 2017;Bakalem et al, 2020).…”
Section: Data Sourcesmentioning
confidence: 99%
“…The species in question belong to the collection of Ayari and Zaâbi (RF in Table 1). 3-Research on polychaetes and studies dealing with macrobenthic fauna, which were published after the last complete inventory of Tunisian polychaetes due to Ayari et al (2009), are revised and collated here, especially the data of Diawara et al (2008), Pérez-Domingo et al (2008, Ayari et al (2009), Zaâbi et al (2009Zaâbi et al ( , 2010Zaâbi et al ( , 2012, Khedhri et al (2014Khedhri et al ( , 2016Khedhri et al ( a, b, 2017, Mosbahi et al (2015Mosbahi et al ( a, b, 2017, Ounifi-Ben Amor et al (2015), Boudaya et al (2019), and Chaibi et al (2019. Other papers were consulted to check the distribution of species in other regions of the Mediterranean (e.g., Castelli et al, 2008;Çinar et al, 2014a, b;Mikac, 2015;Faulwetter et al, 2017;Bakalem et al, 2020).…”
Section: Data Sourcesmentioning
confidence: 99%
“…Chambers et al (2011) described a similar state of art in the Chaetozone species inventory for the Mediterranean Sea, at least until recently. Yet other bitentaculate cirratulids had already been recorded from the Mediterranean coasts over the years (McIntosh 1911;Simboura 1996;Arvanitidis 2000;Simboura & Nicolaidou 2001;Simboura & Zenetos 2002;Çinar et al 2004Zaâbi et al 2009), which had often been identified as Chaetozone sp., and which in turn may encompass more than one species. Most records of the new Chaetozone species from the Mediterranean were previously referred to the type species, C. setosa Malmgren, 1867, or to C. gibber, in technical reports and published papers (Çinar & Ergen 2007;Simboura et al 2010;Chambers et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Protodorvillea egena (Ehlers, 1913) was reported from the Mediterranean (Zenetos et al 2005(Zenetos et al , 2010Coll et al 2010;Occhipinti-Ambrogi et al 2011;Cinar 2013) and first recorded along the Italian coasts, from Sicily (Cantone 2001), likely introduced through the Suez Canal as lessepsian migrant (Amoureux 1983). Protodorvillea kefersteini (McIntosh, 1869) is widely distributed from the North Atlantic to the North Sea and English Channel (Pettibone 1961;Jumars 1974;Perkins 1979;Hartmann-Schröder 1996), Mediterranean (Coll et al 2010;Núñez et al 2013;Çinar et al 2015;Mikac 2015) and the Black Sea (Jakubova 1930;Kurt Sahin et al 2017); P. atlantica was reported from Greece by Vamvakopoulou (1991), although Faulwetter et al (2017) suggested that this record must be considered questionable; in the Mediterranean this species is also known from Tunisia (Zaâbi et al 2009) and the Adriatic Sea (Mikac 2015). Protodorvillea atlantica was firstly described by McIntosh (1885) as Staurocephalus atlanticus, and reported from the Atlantic Ocean by Fauvel (1923).…”
Section: Introductionmentioning
confidence: 99%